Pyrrolidinedithiocarbamic Acid Ammonium Salt Inhibits Apop-tosis and Phenotypic Transformation of Co-Culture of Myeloma Cells and Renal Tubular Epithelial Cells by Reducing the Secretion of Light Chain Protein - Xiaoyan YU; Jie BAO; Xinyu CUI; Fengxia DU; Yuefei WANG; Lili BI; Jun SUN; Ling LI (Tehran University of Medical Sciences, 2020)
Background: We investigate the effects of NFκB inhibitor pyrrolidinedithiocarbamic acid ammonium salt (PDTC) on the viability, apoptosis and cell phenotype of HK-2 cells in the co-culture system of myeloma cells in renal tubular epithelial cells. Methods: This study was performed in Qiqihar Medical University, Qiqihar, China from Jun 2018 to Jan 2019. RPMI-8226 cells and HK-2 cells were inoculated in the co-culture chamber and cultured to establish the co-culture system. An immunoturbidimetric assay was performed to detect κ light chain and λ light chain in RPMI-8226 cells. The effect of PDTC on the secretion of κ light chain and λ light chain of RPMI-8226 cells was detected by immunoturbidimetry and the ratio was calculated. Results: PDTC significantly increased the viability of HK-2 cells. PDTC reduced the apoptosis of renal tubular epithelial cells. After PDTC treatment, the expression of cell surface marker E-cadherin decreased, and the expression of α-SMA increased, which induced the renal interstitial fibrosis. The secretion of κ light chain and λ light chain of RPMI-8226 cells was significantly decreased after the addition of PDTC, but the ratio was not changed. Conclusion: PDTC can inhibit the cell activity, promote apoptosis, and reduce the secretion of secretion of κ light chain and λ light chain through inhibiting the NF-κB pathway activation of myeloma cell RPMI-8226.